2016
DOI: 10.3233/nib-160110
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Gene Expression Alterations in the Brains of Patients with Psychiatric Disorders

Abstract: Abstract.As recent studies have shown that microglia play a key role in inflammation and immunological challenges as well as have broader roles in synaptic modulation in the brain, studies on psychiatric disorders have increasingly focused on microglia. Microglial abnormalities have consistently been observed in psychiatric postmortem brain studies, including altered microglial activation and changes in the protein and mRNA expression levels of microglial marker molecules, such as major histocompatibility comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The microglial activation function in pruning and removing dead cells and releasing humoral factors for immune responses may be involved in the pathogenesis of MDD [ 15 , 54 , 55 ]. Recently, various studies have suggested the essential role of autophagy in microglia in the pathophysiology in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The microglial activation function in pruning and removing dead cells and releasing humoral factors for immune responses may be involved in the pathogenesis of MDD [ 15 , 54 , 55 ]. Recently, various studies have suggested the essential role of autophagy in microglia in the pathophysiology in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Now, investigating the pathology of the human postmortem brain at the molecular level is critical for elucidating the pathophysiology of schizophrenia. For example, abnormal expression level of transcripts related to various biological components including γ-aminobutyric acid (GABA) signaling (3,4), glutamatergic signaling (5), inflammatory system (6), astrocyte (7), oligodendrocyte (8), microglia (9) have been repeatedly reported and it is certain that these system are profoundly included in pathophysiology of schizophrenia. Moreover, effects of schizophrenia-associated single nucleotide polymorphisms (SNPs) on gene expression in the brain have been investigated and the increase of SNPs has been associated with aberrant gene expression and the abnormal brain structure of patients with schizophrenia (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%